Role of CircRNAs_100395 in Proliferation and Metastases of Liver Cancer - Chen, Qiaming (Med Sci Monit, 2019)
BACKGROUND: Circular RNAs (circRNAs) are a kind of noncoding RNA with high cancer-specific expression, and great potential in regulating tumorigenesis. Among these, circRNA_100395 (circ_100395) has been reported to be downregulated in lung cancer, and participates in the process of tumor cell proliferation and metastasis. However, its expression and function in liver cancer remain unknown. MATERIAL/METHODS: Quantitative real-time polymerase chain reaction (RT-qPCR) was used to evaluate the expression level of circ_100395 and microRNAs-1228 (miR-1228) in liver cancer samples and the adjacent non-tumor tissues. Cell proliferation, apoptosis, invasion, migration, and epithelial-mesenchymal transition (EMT) pathway of circ_100395 upregulated cells were analyzed using a Cell Counting Kit-8 (CCK-8), flow cytometry, Transwell assay, and Western blot analysis. RESULTS: We found that circ_100395 was downregulated in cancerous liver tissues relative to the adjacent normal tissues. The overexpression of circ_100395 was negatively associated with tumor differentiation, microvascular invasion, and portal vein tumor thrombosis. However, patients with higher circ_10039 expression tended to have better postoperative disease-free survival time. Moreover, upregulation of circ_100395 in liver cancer cells inhibited cell proliferation, induced apoptosis, then silenced the EMT pathway and reduced migration and invasion abilities, while this anti-tumor effect was significantly reversed by the downstream target, miR-1228. CONCLUSIONS: circ_100395 appears to be a promising therapeutic target for liver cancer.